Production and some properties of crude alkaline proteases of indigenous Central Amazonian rhizobia strains - Oliveira, Arlem Nascimento de (2010)
Two rhizobia strains isolated from soils of the Central Amazonian floodplain produced appreciable quantities of crude alkaline protease extracts with inexpensive carbon and nitrogen sources. These protease crude extracts were optimally active at pH 9.0-11.0. The optimum temperatures were 35 °C for Rhizobium sp. strain R-986 and 55 °C for Bradyrhizobium sp. strain R-993. Protease activities in the crude extracts were enhanced in the presence of 5 mM metal ions, such as Na+, Ca2+, Mg2+ and Mn2+. Rhizobia proteases were strongly inhibited by PMSF, a serine-protease inhibitor. The enzymes were active in the presence of surfactants (SDS and Triton X-100) and stable in oxidizing (H2O2) and reducing agents (β-mercaptoethanol), and organic solvents (acetone, hexane, methanol, 1-propanol and toluene).